2017
DOI: 10.1099/jgv.0.000710
|View full text |Cite
|
Sign up to set email alerts
|

Physical state and copy numbers of HPV16 in oral asymptomatic infections that persisted or cleared during the 6-year follow-up

Abstract: Persistent human papillomavirus (HPV) infection is a key event in HPV-induced carcinogenesis. As part of the prospective Finnish Family HPV Study, we analysed the physical state and viral copy numbers of HPV16 in asymptomatic oral infections that either persisted or cleared during the 6-year follow-up. The persister group comprised 14 women and 7 men with 51 and 21 HPV16-positive brush samples. The clearance group included 41 women and 13 men, with 64 and 24 samples, respectively. Physical state and viral DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…In both genders, persistent oral HPV-16 infections were associated with the mixed or integrated form of HPV-16, while in the clearance groups, episomal HPV-16 predominated. This indicates that HPV-16 integration is a common event, even in asymptomatic oral infections, which might predispose the infected subjects to progressive disease (56). It was also found that in women, persistent (>2 yr) genital HPV infection was predictive for impaired clearance of oral HPV infection (57).…”
Section: Persistent/chronic Hpv Infection Is a Risk For Malignant Tramentioning
confidence: 99%
“…In both genders, persistent oral HPV-16 infections were associated with the mixed or integrated form of HPV-16, while in the clearance groups, episomal HPV-16 predominated. This indicates that HPV-16 integration is a common event, even in asymptomatic oral infections, which might predispose the infected subjects to progressive disease (56). It was also found that in women, persistent (>2 yr) genital HPV infection was predictive for impaired clearance of oral HPV infection (57).…”
Section: Persistent/chronic Hpv Infection Is a Risk For Malignant Tramentioning
confidence: 99%
“…In contrast, few studies (Herberhold et al, 2017;Lorenzi et al, 2017) have shown the value of HPV load as a biomarker in head and neck pathology. Recently, a longitudinal study (Lorenzi et al, 2017) proved that high HPV-16 load is a risk factor for viral persistence and could predict viral integration, a key factor for oncogenesis.…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies have demonstrated that HPV load influences significantly the severity, progression, recurrence, and survival of women affected with cervical cancer, independently of the therapeutic approaches used (Cao et al, 2016;Deng, Feng, Zheng, Huang, & Liu, 2015). In contrast, few studies (Herberhold et al, 2017;Lorenzi et al, 2017) have shown the value of HPV load as a biomarker in head and neck pathology. Recently, a longitudinal study (Lorenzi et al, 2017) proved that high HPV-16 load is a risk factor for viral persistence and could predict viral integration, a key factor for oncogenesis.…”
Section: Introductionmentioning
confidence: 99%
“… 9 11 Therefore, the E2/E6 ratio has been utilized as surrogate markers to discriminate CIN2+. 12 15 However, most published studies with HPV-E2/E6 are based on the cervical tissues by invasive biopsy procedures.…”
Section: Introductionmentioning
confidence: 99%